Characteristics of soils at the IAR research sub-centres at Sheno and Ginchi - Kamara, C.S.; Haque, I.; Beyene, D. (International Livestock Centre for Africa, 1989)
Describes the chemical characteristics of soils at the IAR research sub-centres at Sheno and Ginchi including PH, organic matter, total nitrogen, phosphorus & exchangeable cations, as well as physical characteristics including soil colour, soil texture, bulk density and soil moisture.